Developing the Next Generation of Distance Supervision - Lori A. Goodson; David S. Allen (The Advocate, 2014)
Student teaching has long been an essential component of teacher education programs, and effective supervision is essential for successful internship experiences. Pre-service students’ needs must be weighed against the limitation of time and access for the university supervisor, often a full-time faculty member who has a formidable teaching load and other responsibilities. Additionally, direct, in-person observations can create observer effect, altering the reality of what is actually being observed. This article examines one university’s use of distant supervision utilizing technology to aid in the virtual classroom observations and conferencing to allow an elementary education major to student teach in a rural southwest Kansas school.